ANXIETY IN MAJOR DEPRESSION AND CEREBROSPINAL FLUID FREE GAMMA‐AMINOBUTYRIC ACID. Issue 10 (27th May 2014) - Mann, J. John; Oquendo, Maria A.; Watson, Kalycia Trishana; Boldrini, Maura; Malone, Kevin M.; Ellis, Steven P.; Sullivan, Gregory; Cooper, Thomas B.; Xie, Shan; Currier, Dianne
<x xml:space="preserve">Abstract</x> Background Low gamma‐aminobutyric acid (GABA) is implicated in both anxiety and depression pathophysiology. They are often comorbid, but most clinical studies have not examined these relationships separately. We investigated the relationship of cerebrospinal fluid (CSF) free GABA to the anxiety and depression components of a major depressive episode (MDE) and to monoamine systems. Methods and Materials Patients with a DSM‐IV major depressive episode (N = 167: 130 major depressive disorder; 37 bipolar disorder) and healthy volunteers (N = 38) had CSF free GABA measured by gas chromatography mass spectroscopy. Monoamine metabolites were assayed by high performance liquid chromatography. Symptomatology was assessed by Hamilton depression rating scale. Results Psychic anxiety severity increased with age and correlated with lower CSF free GABA, controlling for age. CSF free GABA declined with age but was not related to depression severity. Other monoamine metabolites correlated positively with CSF GABA but not with psychic anxiety or depression severity. CSF free GABA was lower in MDD compared with bipolar disorder and healthy volunteers. GABA levels did not differ based on a suicide attempt history in mood disorders. Recent exposure to benzodiazepines, but not alcohol or past alcoholism, was associated with a statistical trend for more severe anxiety and lower CSF GABA. Conclusions Lower CSF GABA may explain increasing severity of psychic anxiety in major depression with increasing age. This relationship is not seen with monoamine metabolites, suggesting treatments targeting the GABAergic system should be evaluated in treatment‐resistant anxious major depression and in older patients.